Nonpartisans hold the key: how proximity to utility scale renewable energy projects influences attitudes towards climate mitigation policy - Shan Zhou; Zhengyan Li; Aseem Prakash (Environmental Research Letters, 2025)
Not-in-my-backyard (NIMBY) literature notes public opposition to projects that impose local costs but generate public goods. However, whether NIMBY experience has spillover effects on support for related policy goals remains underexplored. As a typical case of NIMBYism, utility-scale renewable energy projects have faced significant local opposition across the U.S. In this paper, we investigate if an individual’s proximity to such projects correlates with their support for broader climate goals. Drawing on individual responses from three waves of cross-sectional U.S. Nationscape survey data (2019–2021), we constructed a comprehensive dataset by combining them with geocoded information on all utility-scale renewable energy projects for this period, as well as with county-level socioeconomic, political, and policy information. Our regression results show that proximity to wind or solar projects does not significantly influence climate policy preferences among Democrats or Republicans. However, for political Independents, living near wind turbines correlates with reduced opposition to climate policies, specifically large-scale investments for clean energy technology. These findings suggest that climate attitudes linked to renewable energy exposure are contingent on political affiliation. While strong partisans (Democrats and Republicans) remain unaffected by direct exposure to renewable energy projects, Independents—who are less anchored by partisan narratives—are more responsive to personal experience. Exposure to wind power does not necessarily create strong supporters for climate policy, but it shifts Independents away from outright opposition. The results highlight the necessity of more targeted approaches to expand public support for climate policies.